LINKING THE WISHES OF ELDERLY PEOPLE WITH THE INSTRUMENTS OF LEGAL PROTECTION FOR ADULTS - RAOUL-CORMEIL, Gilles (MEDECINE LEGALE DROIT MEDICAL, 2025)
The imperative of human dignity means that we must respect the wishes of the individual, when he or she is able to express him or herself and when it comes to organizing his or her lifestyle. Articles 415, 458 and 459 of the French Civil Code set out a humanist philosophy for the legal protection of adults. Numerous legal instruments enable each individual to organize his or her own legal protection when the time comes to no longer be able to decide for oneself, and to implement the wishes of the now-protected individual within the constraints of what is possible. As human beings and citizens, protected adults must not be subject to constraints other than those inspired by the general interest.